A survey on network attacks and defence-in-depth mechanism by intrusion detection system - Khan, Shakil AKhter; Nizam Uddin (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2006.